The impact of hyperglycaemic crisis episodes on long-term outcomes for inpatients presenting with acute organ injury: A prospective, multicentre follow-up study - Duan, Zixiao; Song, Peiyang; Yang, Cheng; Deng, Liling; Jiang, Youzhao; Deng, Fang; Jiang, Xiaoyan; Chen, Yan; Yang, Gangyi; Ma, Yu; Deng, Wuquan (Frontiers in Endocrinology, 2022)
Background The long-term clinical outcome of poor prognosis in patients with diabetic hyperglycaemic crisis episodes (HCE) remains unknown, which may be related to acute organ injury (AOI) and its continuous damage after hospital discharge. This study aimed to observe the clinical differences and relevant risk factors in HCE with or without AOI. Methods A total of 339 inpatients were divided into an AOI group (n=69) and a non-AOI group (n=270), and their differences and risk factors were explored. The differences in clinical outcomes and prediction models for evaluating the long-term adverse events after hospital discharge were established. Results The mortality among cases complicated by AOI was significantly higher than that among patients without AOI [8 (11.59%) vs. 11 (4.07%), Q = 0.034] during hospitalization. After a 2-year follow-up, the mortality was also significantly higher in patients with concomitant AOI than in patients without AOI after hospital discharge during follow-up [13 (21.31%) vs. 15 (5.8%), Q < 0.001]. The long-term adverse events in patients with concomitant AOI were significantly higher than those in patients without AOI during follow-up [15 (24.59%) vs. 31 (11.97%), Q = 0.015]. Furthermore, Blood β-hydroxybutyric acid (P = 0.003), Cystatin C (P <0.001), serum potassium levels (P = 0.001) were significantly associated with long-term adverse events after hospital discharge. Conclusions The long-term prognosis of HCE patients complicated with AOI was significantly worse than that of HCE patients without AOI. The laboratory indicators were closely correlated with AOI, and future studies should explore the improvement of clinical outcome in response to timely interventions.